Emotion Analysis on Translated Lyrics - Manueke, Ellen Gladys Yunita (ITScience (Information Technology and Science), 2025)
The vowel’s placement of translated lyrics upon the still-the same melody constitutes the emotion of a song. Each syllable has certain stress that needs to be correctly installed into a matching note. Confusing zones are often created when the stress is not suitable to the obstinacy level of the melody. This article analyses the matched placement of syllables upon melody; unmatched figures accidentally creating inconvenience parts of translated song making it loses its feeling. The study reveals that translating song needs to accommodate not only complete structure of words and phrases, but also the stress of every single syllable it brings. The method used in this study is library research, direct-indirect assessment, and analytic. Interviewing and observing are used to support the author’s experiences. This article ends up with a comparative evaluation of two Indonesian translated versions regularly sung, “Blessed Assurance” found in Lagu Sion that proved to be categorized emotionless.